Cardiopulmonary complications during pediatric seizures: A prelude to understanding SUDEP. (5th April 2013) - Singh, Kanwaljit; Katz, Eliot S.; Zarowski, Marcin; Loddenkemper, Tobias; Llewellyn, Nichelle; Manganaro, Sheryl; Gregas, Matt; Pavlova, Milena; Kothare, Sanjeev V.
Summary Purpose Sudden unexpected death in epilepsy (SUDEP) is an important, unexplained cause of death in epilepsy. Role of cardiopulmonary abnormalities in the pathophysiology of SUDEP is unclear in the pediatric population. Our objective was to assess cardiopulmonary abnormalities during epileptic seizures in children, with the long‐term goal of identifying potential mechanisms of SUDEP. Methods We prospectively recorded cardiopulmonary functions using pulse‐oximetry, electrocardiography (ECG), and respiratory inductance plethysmography (RIP). Logistic regression was used to evaluate association of cardiorespiratory findings with seizure characteristics and demographics. Key Findings We recorded 101 seizures in 26 children (average age 3.9 years). RIP provided analyzable data in 78% and pulse‐oximetry in 63% seizures. Ictal central apnea was more prevalent in patients with younger age (p = 0.01), temporal lobe (p < 0.001), left‐sided (p < 0.01), symptomatic generalized (p = 0.01), longer duration seizures (p < 0.0002), desaturation (p < 0.0001), ictal bradycardia (p < 0.05), and more antiepileptic drugs (AEDs; p < 0.01), and was less prevalent in frontal lobe seizures (p < 0.01). Ictal bradypnea was more prevalent in left‐sided (p < 0.05), symptomatic generalized seizures (p < 0.01), and in brain magnetic resonance imaging (MRI) lesions (p < 0.1). Ictal tachypnea was more prevalent in older‐age (p = 0.01), female gender (p = 0.05), frontal lobe (p < 0.05), right‐sided seizures (p < 0.001), fewer AEDs (p < 0.01), and less prevalent in lesional (p < 0.05) and symptomatic generalized seizures (p < 0.05). Ictal bradycardia was more prevalent in male patients (p < 0.05) longer duration seizures (p < 0.05), desaturation (p = 0.001), and more AEDs (p < 0.05), and was less prevalent in frontal lobe seizures (p = 0.01). Ictal and postictal bradycardia were directly associated (p < 0.05). Desaturation was more prevalent in longer‐duration seizures (p < 0.0001), ictal apnea (p < 0.0001), ictal bradycardia (p = 0.001), and more AEDs (p = 0.001). Significance Potentially life‐threatening cardiopulmonary abnormalities such as bradycardia, apnea, and hypoxemia in pediatric epileptic seizures are associated with predictable patient and seizure characteristics, including seizure subtype and duration.